1992
DOI: 10.1093/ejo/14.4.296
|View full text |Cite
|
Sign up to set email alerts
|

The application of computerized tomography (CT) in cases of impacted maxillary canines

Abstract: A comparison is made between conventional X-rays and computerized tomography (CT) based on eight patients with thirteen impacted upper permanent canines. The use of CT yields information which is much more detailed than that observed on conventional X-rays, such as: pathological resorption on adjacent teeth caused by aberrant canines; the localization of the injury and the position of the canine in relation to one or both incisors. The amount of radiation per exposure is still rather high for the CT (Köster an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
15

Year Published

1993
1993
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 0 publications
0
27
0
15
Order By: Relevance
“…A recent systematic review 7 reported that 16% of their included articles dealt with CBCT imaging in orthodontics, and they covered the use of miniscrews in assessing palatal bone thickness, 8,9 safe zones for placement in the maxillary and mandibular arches, 10 fabrication of surgical guides for their placement, 11 cephalometrics, [12][13][14] tooth position 15 and inclination, 16,17 assessment for rapid maxillary expansion, 18 determining skeletal age based on cervical vertebrae morphology, 19 and three-dimensional evaluation of upper-airway anatomy in adolescents. 20 Other orthodontic uses include planning surgical exposure of impacted canines 21 and orthognathic surgery in patients with facial asymmetry, 22 temporomandibular joint (TMJ) disorders, 23 and obtaining additional diagnostic information to assist in treatment planning. 24 Reports of incidental findings on CBCT are sparse.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review 7 reported that 16% of their included articles dealt with CBCT imaging in orthodontics, and they covered the use of miniscrews in assessing palatal bone thickness, 8,9 safe zones for placement in the maxillary and mandibular arches, 10 fabrication of surgical guides for their placement, 11 cephalometrics, [12][13][14] tooth position 15 and inclination, 16,17 assessment for rapid maxillary expansion, 18 determining skeletal age based on cervical vertebrae morphology, 19 and three-dimensional evaluation of upper-airway anatomy in adolescents. 20 Other orthodontic uses include planning surgical exposure of impacted canines 21 and orthognathic surgery in patients with facial asymmetry, 22 temporomandibular joint (TMJ) disorders, 23 and obtaining additional diagnostic information to assist in treatment planning. 24 Reports of incidental findings on CBCT are sparse.…”
Section: Introductionmentioning
confidence: 99%
“…However, CT has some disadvantages: the total radiation dose is high and the equipment is large and very expensive 14) .…”
Section: ⅲ Discussionmentioning
confidence: 99%
“…Current opinion does not ascribe a ny importance to the non-resorption of the deciduous canine as an aetiologic factor in PDC. 20 The findings of Schmuth et al 21 refute the influence of apparently unresorbed deciduous canines. In a computerized tomography (CT) study of 13 aberrant canines they found cases where the CT image revealed root resorption of the deciduous canines which was not apparent on conventional X-ray images of the same area.…”
Section: Why the Procedures Succeeds A) Aetiology Of Pdc And Deciduousmentioning
confidence: 96%